Study on Engineering Performance of Green Porous Sponge Ecological Concrete - Xiao Sun (Advances in Materials Science and Engineering)
To meet the needs of sponge city construction, based on the design method of mix proportion of green porous sponge ecological concrete, the engineering performance of green porous sponge ecological concrete was studied with orthogonal experimental. The results show that the compressive strength of the specimens peaked at the 0.9% admixture of sponge; based on the optimal admixture of sponge, the compressive strength of the specimens peaked at the 12% admixture of mineral powder; compared with the ordinary concrete, the water-retaining property of green porous sponge ecological concrete is twice than ordinary, and green porous sponge ecological concrete has high permeability and low evaporation; under the same external temperature, the maximum temperature of concrete surface is lower than ordinary; and under three work conditions, the volumes of water going through the green porous sponge ecological concrete, respectively, are 1.78 kg/(s·m2), 1.47 kg/(s·m2), and 1.62 kg/(s·m2), and the value of second totally dry condition is minimum because of water blocking affection of the internal sponge. The research results will provide help for the infrastructure construction of sponge city and play an important guiding significance to promote the construction of resource-saving and environment-friendly cities.